KOMUNITAS HARAKAH PADA MASYARAKAT URBAN - Umdatul Hasanah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Several newly decades, it appears the phenomenon of the revival of religious spirit over all social levels, especially on urban society. This phenomenon is indicated by a great number of religious studies and religious morements in cities conducted both conventionally-traditionally and in new forms that have methods and ways which are different from other forms. These groups are frequently called harakah. This articel describes the phenomenon of harakah groups in Cilegon, Banten: Jamaah Tabligh, Jamaah Tarbiyah, Iembaga Dakwah Islamiyah Indonesia (LDII), and Hizhut Tahrir Indonesia. It is clear to demonstrate that the harakah community in Cilegon tends to increase. Keywords: Harakah, Religious Movement, Urban Community, Cilegon City, Jamaah Tahligh, Jamaah Tarbiyah, LDII, and Hizbut Tahrir Indonesia.